Komunikasi Media Pada Era Pandemi Covid-19 Di Sekolah Tinggi Pariwisata Mataram - Dila Ariyogi; Susilo Edi Purwanto; Gusti Ayu Santi Patni R (BICARA: Jurnal Ilmu Komunikasi, 2023)
The communication media in this study is a tool or means used to communicate and convey messages from individuals to other individuals or groups. The formulation of the Media Communication research problem in the COVID-19 Pandemic Era at the Mataram Tourism College, namely (1) What is the form of media communication at the Mataram Tourism College in the COVID-19 pandemic era? (2) What is the process of realizing media communication at the Mataram Tourism College during the COVID-19 pandemic era? (3) What needs to be evaluated from the realization of media communication at the Mataram Tourism College during the COVID-19 pandemic era? The purpose of this study is expected to be able to adjust and improve the quality of forms and processes of online communication in universities. In this study, two theories were used to solve the problem: Communication Media, Form of Communication.This research is descriptive qualitative research, and the data collection techniques were observation, interviews, and documentation. This study showed that media communication at STP Mataram uses Whatsapp to communicate and provide information related to lecturing and other general information, Google Classroom to provide materials and assignments and Zoom Meetings to discuss teaching material and conduct online meetings. The lack of teaching staff competence in using and implementing online media is a factor that needs to be taken seriously. It needs immediate action by providing socialization about online media communication. The problem with students' internet signal is a big obstacle that needs to be considered, so the lecturers need to provide teaching material to be shared through Google Classroom. The process of online lecturing can be recorded to be used for the student to learn.